Protection against insect predation during fruit development: the role of fleshy fruit wings of three species of Zygophyllum in the cold desert of Central Asia - Xie, Kaiqing; Qiu, Juan; Mamut, Jannathan; Li, Yuting; Tan, Dunyan (Frontiers in Plant Science, 2023)
Fruit wings serve various ecological functions, including facilitating wind dispersal, providing physical protection to seeds, and regulating seed germination. While many studies have reported the role of fruit wings in plants, little is known about their protective function during fruit development. In this study, winged fruits damaged by insects in natural populations of three Zygophyllum species (Z. potaninii, Z. lehmannianum and Z. macropterum) were investigated. We measured and compared the percentage of damaged winged fruits, seed set, seed mass, seed germination, and seedling growth of different insect herbivory categories. The results revealed that the percentage of winged fruits with damaged wings only (low predation) was significantly higher than that of with damaged both fruit wings and fruit bodies (high predation). Furthermore, winged fruits with low predation had significant higher seed set, seed mass, seed germination, and dry mass and relative growth rate (RGR) in the seedlings which grown from the seeds, than that from winged fruits with high predation. These results demonstrate that the presence of the fruit wings may provide protection for the seeds to alleviate harm from insect predation before dispersal. These findings provide new insights into the function of fruit wings and the reproductive strategies of desert plants.